2022
DOI: 10.3390/cells11172698
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Role of Adipose Tissue HDAC9 in Diet-Induced Obesity and Metabolic Dysfunction

Abstract: Obesity is a major risk factor for both metabolic and cardiovascular disease. We reported that, in obese male mice, histone deacetylase 9 (HDAC9) is upregulated in adipose tissues, and global deletion of HDAC9 protected against high fat diet (HFD)-induced obesity and metabolic disease. Here, we investigated the impact of adipocyte-specific HDAC9 gene deletion on diet-induced obesity in male and female mice. The HDAC9 gene expression was increased in adipose tissues of obese male and female mice and HDAC9 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Despite the well-known differences in metabolic physiological systems, diseases and treatment outcomes among sex, the models used in the study of obesity are limited by the underrepresentation of females [ 23 , 24 , 25 ], as the presence of both sexes in animal as well as in cell-based studies has been recently considered [ 26 ]. In this context, it is necessary to examine the sex-specific characteristics of glucose metabolism as they are clearly involved in regulatory mechanisms in clinical pathologies including metabolic syndrome, obesity and T2D [ 27 , 28 ]. Obesity superimposed on aging drastically alters the inflammatory status, promoting the development of metabolic diseases, such as T2D, metabolic syndrome and cardiovascular disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-known differences in metabolic physiological systems, diseases and treatment outcomes among sex, the models used in the study of obesity are limited by the underrepresentation of females [ 23 , 24 , 25 ], as the presence of both sexes in animal as well as in cell-based studies has been recently considered [ 26 ]. In this context, it is necessary to examine the sex-specific characteristics of glucose metabolism as they are clearly involved in regulatory mechanisms in clinical pathologies including metabolic syndrome, obesity and T2D [ 27 , 28 ]. Obesity superimposed on aging drastically alters the inflammatory status, promoting the development of metabolic diseases, such as T2D, metabolic syndrome and cardiovascular disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adipogenic differentiation of preadipocytes derived from human subcutaneous adipose tissue has been negatively correlated with body mass index [36]. Accordingly, we recently showed that body mass index positively correlates with subcutaneous adipose tissue HDAC9 expression in humans, who typically live in climate‐controlled environments [37], suggesting that our findings are potentially translationally relevant.…”
Section: Discussionmentioning
confidence: 73%
“…Studies have found that CEACAM1 [237], STAT1 [238], ARG1 [239], TLR4 [240], LRRK2 [241], ABCA1 [242], PTGS2 [243], CYP2D6 [244], JAK2 [245], TLR2 [246], DUSP6 [247], CYP1B1 [248], CCR1 [249], HDAC9 [250], LATS2 [251], IL1RN [252], GCH1 [253], PELI1 [254], EGR1 [255], HIPK3 [256], CCR2 [257], GCLC (glutamate-cysteine ligase catalytic subunit) [258], KLF3 [259], VEGFA (vascular endothelial growth factor A) [260], ITGB1 [261], RASA1 [262], PTPN12 [263], SNRK (SNF related kinase) [264], PRKAR1A [265], LDLR (low density lipoprotein receptor) [266], SIRT1 [267], NOD2 [268], VCAN (versican) [269], TET2 [270], PFKFB2 [271], ZBTB20 [272], MYBL2 [273], PF4 [274], VEGFB (vascular endothelial growth factor B) [275], CCR7 [276], PRDX2 [277], HSPB1 [278], ZNF791 [279], IGFBP4 [280], ESF1 [281], SNHG8 [282], LGALS3 [283] and LGMN (legumain) [284] are altered expression in myocardial infarction. Altered expression of CEACAM1 [176], ACSL1 [285], STAT1 [286], TLR4 [287], ABCA1 [288], TLR5 [183], F2RL1 [289], CYP2D6 [290], PDK4 [291], RNF213 [186], JAK2 [292], TLR8 [189], NOTCH2 [293], CENPJ (centromere protein J) [294], FNIP1 [295], TLR2 [296], KIDINS220 [297], DUSP6 [298], CYP1B1 [299], S1PR3 [300], NCOA2 [301], HDAC9 [302], PELI1 [303], EGR1 [304], HIF1A [305], CCR2 [306], IR...…”
Section: Discussionmentioning
confidence: 99%